China’s “Belt and Road” and Indonesia: Challenges and Opportunities - Alamsyah, Mirah Satria; Amalia, Ridha (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2023)
Lately Indonesia and China are in a good relationship. At the same time, China launched the Belt and Road Initiative which is another form of ancient Silk Road. During the Silk Road era, Indonesia had an important role as a 'spice island'. So in line with the Belt and Road Initiative, China expects Indonesia to take part in this initiative. However, the good relationships between these two countries are not enough to predict the path of this initiative. Therefore this paper aims to discuss the Challenges and opportunities for Indonesia in the Belt and Road Initiative.